Israel economic development, past progress and plan for the future: final draft - State of Israel (Jerusalem : Prime Minister's Office, Economic Planning Office, 1968)
This book is on Israel economic development, the jewish population and the non-Jewish population, the labour forces, employment and unemployment.
Translated from the Hebrew.
oo 01/08/2018
Loans